The role of labor markets for euro area monetary policy - Kai Christoffel; Keith Kuester; Tobias Linzert (European Central Bank (ECB), 2009)
In this paper, we explore the role of labor markets for monetary policy in the euro area in a New Keynesian model in which labor markets are characterized by search and matching frictions. We first investigate to which extent a more flexible labor market would alter the business cycle behaviour and the transmission of monetary policy. We find that while a lower degree of wage rigidity makes monetary policy more effective, i.e. a monetary policy shock transmits faster onto inflation, the importance of other labor market rigidities for the transmission of shocks is rather limited. Second, having estimated the model by Bayesian techniques we analyze to which extent labor market shocks, such as disturbances in the vacancy posting process, shocks to the separation rate and variations in bargaining power are important determinants of business cycle fluctuations. Our results point primarily towards disturbances in the bargaining process as a significant contributor to inflation and output fluctuations. In sum, the paper supports current central bank practice which appears to put considerable effort into monitoring euro area wage dynamics and which appears to treat some of the other labor market information as less important for monetary policy.
Keywords: E32; E52; J64; C11; 330; bargaining; Bayesian estimation; Labor market; wage rigidity; Geldpolitik; Geldpolitische Transmission; Arbeitsmarktflexibilität; Lohnrigidität; Konjunktur; Eurozone; Makroökonometrie; Neoklassische Synthese; Schätzung; Theorie; EU-Staaten